Boletín y elegía de las mitas o la culminación de la vanguardia indigenista en el Ecuador. Un ejercicio de lectura roblesiano (In Memoriam: Cuatro autores en tiempo presente; Humberto E. Robles, Juan Valdano, Eliécer Cárdenas Espinosa y Jorge Velasco Mackenzie. Testimonios, legados y relecturas) - Balladares, María Auxiliadora (2022)
Some of the postulates reviewed and proposed in Humberto E. Robles’ study on the notion of the vanguard in Ecuador set the tone for a new exercise of critical reading of César Dávila Andrade’s Boletín y elegía de las mitas. This paper proposes reading the Boletín as an exercise of culmination of the notion of the Latin American vanguard proposed in the 1930s by Jorge Carrera Andrade and reviewing two of the central antecedents in the poetic tradition of the Indian theme in Ecuador: José Joaquín de Olmedo and Jorge Carrera Andrade himself.